Moment Tensor Solutions A Useful Tool for Seismotectonics (Springer Natural Hazards,, 2018)
The book first focuses on the explanation of the theory about focal mechanisms and moment tensor solutions and their role in the modern seismology. The second part of the book compiles several state-of-the-art case studies in different seismotectonic settings of the planet. The assessment of seismic hazard and the reduction of losses due to future earthquakes is probably the most important contribution of seismology to society. In this regard, the understanding of reliable determination seismic source and of its uncertainty can play a key role in contributing to geodynamic investigation, seismic hazard assessment and earthquake studies. In the last two decades, the use of waveforms recorded at local-to-regional distances has increased considerably. Waveform modeling has been used also to estimate faulting parameters of small-to-moderate sized earthquakes. .